Skin-to-Skin Contact in Cesarean Birth and Duration of Breastfeeding: A Cohort Study - Andrea Guala; Luigina Boscardini; Raffaella Visentin; Paola Angellotti; Laura Grugni; Michelangelo Barbaglia; Elise Chapin; Eleonora Castelli; Enrico Finale (The Scientific World Journal)
Early skin-to-skin contact (SSC) after birth is a physiological practice that is internationally recommended and has well-documented importance for the baby and for the mother. This study aims to examine SSC with a cohort of mothers or fathers in the operating room after a Cesarean section (C-section) and its relationship with duration of breastfeeding. From January 1, 2012, to December 31, 2012, at the Castelli Hospital in Verbania, Italy, a Baby Friendly designated hospital, 252 consecutive women who had a C-section were enrolled in the study and followed for 6 months. The sample was later divided into three groups depending on the real outcomes in the operating room: SSC with the mother (57.5%), SSC with the father (17.5%), and no SSC (25%). Our study showed a statistical association between skin-to-skin contact with the mother and the exclusive breastfeeding rates on discharge. This effect is maintained and statistically significant at three and six months, as compared to the groups that had paternal SSC or no SSC. After a C-section, skin-to-skin contact with the mother can be an important practice for support, promotion, and duration of breastfeeding.